factorise: -
(l+m) ² - 4lm
Answers
Answered by
48
l^2 + m^2 + 2lm - 4lm
l^2 + m^2 - 2lm
(l-m)^2
l^2 + m^2 - 2lm
(l-m)^2
Answered by
41
hope u understand this one.
![(l {}^{2} + m {}^{2} + 2lm) - 4lm = l {}^{2} + m {}^{2} + 2lm - 4lm = l {}^{2} + m {}^{2} - 2lm = l {}^{2} + m {}^{2} - 2 \times l \times m = (l - m) { }^{2} (l {}^{2} + m {}^{2} + 2lm) - 4lm = l {}^{2} + m {}^{2} + 2lm - 4lm = l {}^{2} + m {}^{2} - 2lm = l {}^{2} + m {}^{2} - 2 \times l \times m = (l - m) { }^{2}](https://tex.z-dn.net/?f=%28l+%7B%7D%5E%7B2%7D++%2B+m+%7B%7D%5E%7B2%7D++%2B+2lm%29+-+4lm+%3D+l+%7B%7D%5E%7B2%7D++%2B+m+%7B%7D%5E%7B2%7D++%2B+2lm+-+4lm+%3D+l+%7B%7D%5E%7B2%7D++%2B+m+%7B%7D%5E%7B2%7D++-+2lm+%3D+l+%7B%7D%5E%7B2%7D++%2B+m+%7B%7D%5E%7B2%7D++-+2+%5Ctimes+l+%5Ctimes+m+%3D+%28l+-+m%29+%7B+%7D%5E%7B2%7D+)
Similar questions